1969
DOI: 10.1113/jphysiol.1969.sp008926
|View full text |Cite
|
Sign up to set email alerts
|

The effect of membrane polarization on the time course of the end‐plate current in frog sartorius muscle

Abstract: SUMMARY1. Intracellular recordings of the end-plate current at different membrane potentials were made, using a voltage-clamp technique.2. When the membrane potential is varied between about +40 and -120 mV, the half-decline time of the end-plate current increases from about 0-6 msec to about 1*6 msec.3. It is suggested that the stability of receptor-mediator complex is affected by the membrane potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0
2

Year Published

1973
1973
1990
1990

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 13 publications
6
44
0
2
Order By: Relevance
“…According to the analysis of Magleby & Stevens (1972) the number of channels opened by the transmitter at the neuromuscular junction is a function of membrane potential, and this accounts for the non-linearity in the relationship between membrane potential and peak end-plate current, in response to a nerve stimulus, described by Takeuchi & Takeuchi (1959, 1960 and Kordas (1969). It may be noted however that the voltage dependence deduced by Magleby & Stevens (see also Anderson & Stevens, 1973) should give rise to an effect in the opposite direction in the relationship between membrane potential and current produced by a constant concentration of agonist.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the analysis of Magleby & Stevens (1972) the number of channels opened by the transmitter at the neuromuscular junction is a function of membrane potential, and this accounts for the non-linearity in the relationship between membrane potential and peak end-plate current, in response to a nerve stimulus, described by Takeuchi & Takeuchi (1959, 1960 and Kordas (1969). It may be noted however that the voltage dependence deduced by Magleby & Stevens (see also Anderson & Stevens, 1973) should give rise to an effect in the opposite direction in the relationship between membrane potential and current produced by a constant concentration of agonist.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed information however is lacking. Even at the frog neuromuscular junction where the evidence that there is little rectification is most direct (Fatt & Katz, 1951;Takeuchi & Takeuchi, 1959; Kordas, 1969;Magleby & Stevens, 1972;Anderson & Stevens, 1973) the interpretation is somewhat uncertain. The simultaneous movements of two ions, sodium and potassium, are involved (Takeuchi & Takeuchi, 1960) and it might be supposed that the corresponding path-B.…”
Section: Introductionmentioning
confidence: 99%
“…Gage and Armstrong (1968) voltage clamped the neuromuscular junction at membrane potentials equal to EK and EN,, using TTX to block action potentials and, from the large difference in the time constant of decay for the miniature EPC's at the two voltage levels, suggested that the transmitter opened separate channels for Na+ and K+ with different time-courses. Kordas (1969) treated muscles with glycerol to block contraction of the muscle fiber over a wide range of voltage clamp potentials and showed a continuous decrease in the time constant for decay of the EPC as the' membrane was held at more depolarizing membrane potentials. If two channels were opened with different time-course, there would be some potentials at which the EPC would be diphasic; however, no diphasic EPC's were seen.…”
Section: Time-course Of Synaptic Current At Different Levels Of Membrmentioning
confidence: 99%
“…On the other hand, Kordas (1969) suggested the possibility that the relation ship obtained in glycerol treated muscle, which is similar to that in procaine, might be explained by a change in the receptor-ACh interaction. It is possible that the polarizing current changes the interaction of positively charged PG with some receptor in the end-plate directly or by altering the concentration of PG at the surface of the end-plate.…”
Section: Discussionmentioning
confidence: 97%